Verifying systems of resource-bounded agents - Alechina, Natasha; Logan, Brian (Springer Verlag, 2016)
Approaches to the verification of multi-agent systems are typically based on games or transition systems defined in terms of states and actions. However such approaches often ignore a key aspect of multi-agent systems, namely that the agents’ actions require (and sometimes produce) resources. We briefly survey previous work on the verification of multi-agent systems that takes resources into account, and outline some key challenges for future work.